Genome-wide association analysis for severity of coronary artery disease using the gensini scoring system - Zeller, Tanja; Kleber, Marcus E.; März, Winfried (Frontiers in Cardiovascular Medicine, 2017)
Coronary artery disease (CAD) has a complex etiology involving numerous environmental and genetic factors of disease risk. To date, the genetic 9p21 locus represents the most robust genetic finding for prevalent and incident CAD. However, limited information is available on the genetic background of the severity and distribution of CAD. CAD manifests itself as stable CAD or acute coronary syndrome. The Gensini score quantifies the extent CAD but requires coronary-angiography. Here, we aimed to identify novel genetic variants associated with Gensini score severity and distribution of CAD. A 2-stage approach including a discovery and replication stage was used to assess genetic variants. In the discovery phase, a meta-analysis of genome-wide association data of 4,930 CAD-subjects assessed by the Gensini score was performed. Selected single nucleotide polymorphisms (SNPs) were replicated in 2,283 CAD-subjects by de novo genotyping. Five SNPs, located on chromosome 2 and 9, were selected for replication. SNP rs133349, located within the know CAD-locus on chromosome 9p21, was confirmed as a risk locus for CAD severity. No additional strong susceptibility loci of CAD severity were identified.